Hydraulic variability of three temperate broadleaf tree species along a water availability gradient in central Europe. Issue 4 (6th June 2021) - Fuchs, Sebastian; Leuschner, Christoph; Mathias Link, Roman; Schuldt, Bernhard
Summary: Plant hydraulic traits are key for understanding and predicting tree drought responses. Information about the degree of the traits' intra‐specific variability may guide the selection of drought‐resistant genotypes and is crucial for trait‐based modelling approaches. For the three temperate minor broadleaf tree species Acer platanoides, Carpinus betulus and Tilia cordata, we measured xylem embolism resistance ( P 50 ), leaf turgor loss point ( P TLP ), specific hydraulic conductivity ( K S ), Huber values (HVs), and hydraulic safety margins in adult trees across a precipitation gradient. We further quantified trait variability on different organizational levels (inter‐specific to within‐canopy variation), and analysed its relationship to climatic and soil water availability. Although we observed a certain intra‐specific trait variability (ITV) in safety‐related traits ( P 50, P TLP ) with higher within‐tree and between‐tree than between populations variability, the magnitude was small compared to inter‐specific differences, which explained 78.4% and 58.3% of the variance in P 50 and P TLP, respectively. In contrast, efficiency‐related traits ( K S, HV) showed a high ITV both within populations and within the crowns of single trees. Surprisingly, the observed ITV of all traits was neither driven by climatic nor soil water availability. In conclusion, the high degree of conservatism in safety‐related traits highlights their potential for trait‐based modelling approaches.